Image Edge Feature Extraction and Refining Based on Genetic-Ant Colony Algorithm - Xing Zhang; Shuai Liu (Universitas Ahmad Dahlan, 2015)
Edge is composed by a collection of its nearby pixels which has a step change or changes in roof, an image is an information system and most of its information comes from the edges. This paper gives a brief overview of the status and the importance of image edge detection and introduces the research status of the image edge detection. After that, it introduces the basic principle and the main steps of the genetic algorithm and ant colony algorithm. On the basis of these, the paper proposed a new hybrid algorithm for the image edge extraction and refining, which combined the genetic algorithm and ant colony algorithm. Through the analysis of the time-speed graph of the genetic algorithm and the ant colony algorithm, we can find the best fusion point between the genetic algorithm and the ant colony algorithm. The experiment indicated the proposed hybrid algorithm can make the full use of the image information, the simulation time is shorter, the image edge is more continuous, and preserved the outline of original image more completely.